The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1093/europace/euv333
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic relevance of the interaction between short-term, metronome-paced heart rate variability, and inflammation: results from the population-based CARLA cohort study

Abstract: A change in TNF-α levels or the autonomic nervous system influences the mortality risk through both entities simultaneously. Thus, TNF-α and HRV need to be considered when predicating mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…When comparing our data to theirs, our control group was younger and with more female donors, and we observed lower levels of sTNFR1 but higher levels of sTNFR2, but in both studies, the sTNFR levels in the patients were significantly higher than in the control group. However, it has to be noted that the levels of sTNFR1 reported by us and others 16 18 in STEMI patients are relatively similar to the ones reported in prospective studies in patients with stable CAD 7 , 8 , 20 , and also to levels reported in population-based studies in older adults 9 , 11 13 . Thus, the level of sTNFR1 may not be of diagnostic interest on the population level in this age group.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…When comparing our data to theirs, our control group was younger and with more female donors, and we observed lower levels of sTNFR1 but higher levels of sTNFR2, but in both studies, the sTNFR levels in the patients were significantly higher than in the control group. However, it has to be noted that the levels of sTNFR1 reported by us and others 16 18 in STEMI patients are relatively similar to the ones reported in prospective studies in patients with stable CAD 7 , 8 , 20 , and also to levels reported in population-based studies in older adults 9 , 11 13 . Thus, the level of sTNFR1 may not be of diagnostic interest on the population level in this age group.…”
Section: Discussionsupporting
confidence: 85%
“…For sTNFR2, only one study report values as high as ours 8 , while the other studies that included this marker 7 , 11 , 12 , 16 18 , 20 report levels more similar to the ones in our control group. The reason for this is unclear, all these studies have used ELISA kits from the same manufacturer, and even though analyses have been performed in plasma in some 12 , 13 , 18 , 20 and in serum in others 10 , 12 , 16 , 17 this did not seem to have created any consistent differences in levels. Also, we did not observe any differences in levels between the investigated time points, while Nilsson et al 18 report increased levels at 24 h and Paccalet et al shows increasing levels up to 48 h followed by a decrease towards admission levels after one month 16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, higher HRV might predict more prolonged survival in cancer patients due to the effect of vagus nerve activity on cancer progression. Evidence also showed that the interaction of HRV and inflammatory mediators such as TNF-α and IL-6 is associated with cardiovascular mortality in a population-based CARLA cohort study [ 25 ]. Moreover, the release of inflammatory cytokines and chemokines following TBI can alter sleep [ 26 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated increased all-cause and cardiovascular mortality in patients with various diseases and higher levels of sTNF-R1 [ 7 12 ]. In the general population, elevated levels of sTNF-R1 were associated with all-cause and cardiovascular mortality after adjustment for lifestyle factors, inflammation due to chronic diseases, and established cardiovascular risk factors [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%